Use of Ultrasonography to Age Pregnancy in Early Gestation in Dairy Cows - Klibs N.A. Galvão (EDIS, 2012)
Using ultrasonography for diagnosis and aging of pregnancy is becoming more widespread among bovine practitioners because it can be done earlier than by traditional methods, and because it can be used to monitor fetal development and determine fetal age and sex. This 3-page fact sheet presents a detailed measurement of the amniotic vesicle from 27 to 34 days after breeding so a more precise aging of early pregnancies can be performed. Written by Klibs N.A. Galvão and published by the UF Department of Veterinary Medicine-Large Animal Clinical Sciences, May 2012.